Fireproof door filling material and application thereof
By preparing composite fillers and enhancing and foaming with materials such as phthalic anhydride polyester polyol, the problem of insufficient compression and sound insulation performance of existing fire door fillers is solved, and higher sound absorption performance and structural stability are achieved.
Patent Information
- Application Number
- CN202510147034.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-02-11
- Publication Date
- 2025-03-14
- Estimated Expiration
- 2045-02-11
AI Technical Summary
The compression performance and sound insulation performance of existing fire door fillers need to be further improved.
By preparing a composite filler, including a modified mixed filler, polyethylene glycol, modified phosphate and deionized water, it is then enhanced with a mixed material composed of phthalic anhydride polyester polyol, polyethylene glycol, hydroxy silicone oil and urea, and reacted with isocyanate after foaming treatment by foaming additives to form a foam with a closed cell structure.
The sound absorption and noise reduction performance and compression stress of the filler material are improved, and the structural stability and flame retardant performance of the material are enhanced.
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of foam filling material processing, and in particular to a fire door filling material and application thereof. Background Art
[0002] With the continuous advancement of modern construction technology and people's increasing demand for safety, fire doors, as important safety facilities in buildings, have increasingly stringent performance requirements to ensure that in emergency situations such as fires, they can effectively prevent the spread of fire while maintaining the stability and integrity of the structure.
[0003] In the prior art, a preparation method of a brucite-based lightweight fireproof door filler with publication number CN107673728A includes raw material preparation, yew bark fiber modification, brucite modification and filler preparation. The brucite is modified under specific conditions and has good compatibility in the mixed material. Due to the synergistic effect of material A and graphite oxide colloid, the obtained filler has improved mechanical properties compared with brucite, and the heat release rate is reduced. The material has a fine and uniform microporous structure as a whole, which not only reduces the density of the material, but also can play an internal buffering role when strong thermal expansion and contraction occur. The fireproof performance reaches the non-combustible A1 level, the performance is stable, and the application of brucite in the field of fire prevention is realized. The dry density is 240-280kg / m³, which is convenient for installation and use, and easy to promote and use.
[0004] Fire door fillers are filled in the frame of the fire door. On the one hand, they increase the overall flame retardant performance of the fire door. Its more important function is to connect and support the two panels to prevent the panels from being damaged when they are subjected to external collisions. However, traditional filling materials are mostly foam materials, which are easily compressed when subjected to collisions, causing stress damage to the panels. In addition, fire doors are usually installed in corridors adjacent to the outside world and need to have good sound insulation properties to isolate them from external noise pollution. Fire doors often use fireproof foam boards as fillers, and the density of the fillers is relatively large. The sound absorption and sound insulation effects of the fire door fillers need to be further improved.
[0005] In view of the technical defects in this aspect, a solution is now proposed. Summary of the invention
[0006] The object of the present invention is to provide a fire door filling material and application thereof, so as to solve the technical problem in the prior art that the compression performance and sound insulation performance of fire door filling materials need to be further improved.
[0007] The object of the present invention can be achieved by the following technical solution: A fire door filling material, the fire door filling material is processed by the following steps:
[0008] S1, mixing and stirring the modified mixed filler, polyethylene glycol, modified phosphate ester and deionized water, adding phosphoric acid to the reaction system, adjusting the system pH to 3-4, raising the temperature of the reaction system to 70-80°C, keeping the temperature for reaction for 2-3h, and post-treating to obtain a composite filler;
[0009] S2, mixing phthalic anhydride polyester polyol, polyethylene glycol, hydroxy silicone oil, composite filler, urea, and foaming aid to obtain a pre-foamed material;
[0010] S3, under the protection of inert gas, adding diisocyanate to the pre-foamed material, stirring and dispersing until the pre-foamed material is generated by bubbles, to obtain a foamed material;
[0011] S4, injecting the foaming material into the mold, and curing it after foaming to prepare the filling material.
[0012] Furthermore, in step S1, the amount ratio of the modified mixed filler, polyethylene glycol, modified phosphate and deionized water is 3g:6g:1g:50mL, the polyethylene glycol is PEG-400, and the post-treatment includes: after the reaction is completed, the temperature of the reaction system is lowered to room temperature, filtered, the filter cake is washed with deionized water until it is neutral and then dried, the filter cake is transferred to a drying oven at a temperature of 65-75°C, and vacuum dried to constant weight to obtain a composite filler.
[0013] The synthetic reaction mechanism of composite fillers is:
[0014] In the reaction, protons are provided under acidic conditions to combine with oxygen atoms in the epoxy group, making it positively charged and more susceptible to attack by the nucleophilic hydroxyl group, thereby opening the epoxy ring and forming a relatively stable carbon ion intermediate. Subsequently, this carbon ion intermediate can further react with another hydroxyl molecule or other nucleophilic reagent to generate alcohol compounds and release water molecules, thereby modifying the modified mixed filler and the modified phosphate ester molecule with polyethylene glycol to prepare a composite filler having the polyethylene glycol-modified modified mixed filler and the modified phosphate ester.
[0015] Furthermore, in step S2, the weight ratio of the phthalic anhydride polyester polyol, polyethylene glycol, hydroxy silicone oil, composite filler, urea and foaming aid is 55-65:20-30:8-13:15-18:5-7:10-15, the polyethylene glycol is PEG-1000, and the foaming aid is composed of monofluorodichloroethane, triethylenediamine and dipropylene glycol in a dosage ratio of 5g:2g:7mL.
[0016] Furthermore, in step S3, the molar amount of the diisocyanate is half of the total molar amount of the hydroxyl group and the amino group in the pre-foamed material, and the diisocyanate is one or more of isophorone diisocyanate, meta-phenylenediisocyanate, o-phenylenediisocyanate, toluene 2,6-diisocyanate, and meta-phenylenediisocyanate.
[0017] Furthermore, in step S4, the aging operation includes: placing the foamed and cured foam in a curing box at a temperature of 80-90°C and a humidity of 60-80% for 10-12 hours, and then transferring it to a drying box at a temperature of 60-70°C and drying it to constant weight to obtain a filling material.
[0018] Further, the modified mixed filler is processed by the following steps:
[0019] A1, mixing mullite fiber, hollow glass microspheres and expanded graphite uniformly to obtain a mixed filler;
[0020] A2. Mix and stir the mixed filler, tetrahydrofuran and KH-560, raise the temperature of the reaction system to 55-65°C, add a catalyst to the reaction system, keep the temperature for 90-120 minutes, and post-treat to obtain a modified mixed filler.
[0021] Furthermore, in step A1, the weight ratio of mullite fiber, hollow glass microsphere and expanded graphite is 5:2:2; in step A2, the amount ratio of the mixed filler, tetrahydrofuran, KH-560 and catalyst is 4g:20mL:3g:5mL, and the catalyst is composed of 0.3-0.5mol / L sodium hydroxide solution and sodium stearate in an amount ratio of 3mL:1g. The post-treatment includes: after the reaction is completed, the temperature of the reaction system is lowered to room temperature, filtered, the filter cake is washed with purified water until neutral and then dried, and the filter cake is transferred to a drying oven at a temperature of 60-70°C, and vacuum dried to constant weight to obtain a modified mixed filler.
[0022] Furthermore, the preparation method of the modified phosphate ester is: under the protection of inert gas, diethyl (chlorocarbonyldifluoromethyl)phosphonate, 1-(oxirane-2-yl)ethane-1,2-diol, tetrahydrofuran and potassium carbonate are mixed and stirred, the temperature of the reaction system is increased to 40-45°C, the reaction is kept warm for 4-6 hours, and post-processed to obtain the modified phosphate ester.
[0023] The synthetic reaction formula of modified phosphate ester is:
[0024] ;
[0025] The synthetic reaction mechanism of modified phosphate ester is:
[0026] During the reaction, potassium carbonate is used as a catalyst to react the acyl chloride group on the diethyl (chlorocarbonyldifluoromethyl)phosphonate molecule with the hydroxyl group on the 1-(oxirane-2-yl)ethane-1,2-diol molecule to undergo a nucleophilic substitution reaction to form an ester bond, and diethyl phosphate modification is formed at the two phenolic hydroxyl positions of the 1-(oxirane-2-yl)ethane-1,2-diol to prepare a modified phosphate ester;
[0027] The mass spectrometry data of modified phosphate esters are: m / z: 532.0886 (100.0%), 533.0920 (17.3%),
[0028] 534.0929(2.3%),534.0954(1.4%).
[0029] Furthermore, the amount ratio of the diethyl (chlorocarbonyldifluoromethyl)phosphonate, 1-(oxirane-2-yl)ethane-1,2-diol and potassium carbonate is 2 mol:1 mol:1.1 mol, the amount ratio of the diethyl (chlorocarbonyldifluoromethyl)phosphonate and tetrahydrofuran is 1 g:10 mL, and the post-treatment includes: keeping the reaction system at 40-45° C., removing low-boiling substances under reduced pressure, lowering the temperature of the reaction system to room temperature, adding anhydrous ethanol to the reaction system, lowering the temperature of the reaction system to 5-10° C., stirring and dispersing for 20-30 minutes, filtering, transferring the filtrate to a rotary evaporator with a water bath temperature of 60-70° C., and removing low-boiling substances under reduced pressure to obtain a modified phosphate.
[0030] The present invention also provides an application of the fire door filling material, and the fire door filling material is applied to the manufacture of the fire door.
[0031] The present invention has the following beneficial effects:
[0032] 1. The fire door filling material of the present invention is prepared by modifying a mixed filler by KH-560, modifying an epoxy group on the surface of an inorganic filler, and compounding the modified mixed filler modified by the epoxy group and the modified phosphate modified by the epoxy group by polyethylene glycol to obtain a composite filler having the modified mixed filler modified by polyethylene glycol and the modified phosphate ester, and then reinforcing a mixed material composed of phthalic anhydride polyester polyol, polyethylene glycol-1000, hydroxy silicone oil and urea with the composite filler, and then foaming the mixed material with a foaming aid and reacting with isocyanate to generate a foam with a closed-cell structure, thereby obtaining a foam structure with a high porosity, improving the sound absorption and noise reduction performance of the filling material, and reacting the active functional groups on the molecules of phthalic anhydride polyester polyol, polyethylene glycol-1000, hydroxy silicone oil and the composite filler with isocyanate to form a cross-linked network structure, thereby improving the structural stability of the material, so that the material has good compressive stress.
[0033] 2. The fire door filling material of the present invention uses a combination of mullite fiber, hollow glass microspheres and expanded graphite as a mixed filler, and uses mullite fiber as a skeleton support. The hollow structure of the low-density hollow glass microspheres can absorb and disperse external forces, thereby improving the compression toughness of the material. Expanded graphite is filled between the mullite fiber and the hollow glass beads as an inorganic nanopowder, thereby reducing the influence of the addition of expanded graphite on the mechanical strength of the material. The mixed filler is modified and then compounded with polyethylene glycol to prepare a composite filler, thereby improving the dispersibility of the composite filler in the foaming material, making it easier for the inorganic filler to be evenly dispersed in the foaming material to form a stable support, thereby improving the compression performance of the filling material. Modified phosphate is added to the composite filler. The modified phosphate is a phosphorus-based flame retardant. The mullite fiber can maintain a stable structure at high temperature, is not easy to burn, and can absorb a large amount of heat, thereby reducing the combustion temperature of the material. The expanded graphite will expand rapidly at high temperature to form a dense carbon layer, isolate oxygen, and prevent the spread of flames. The three cooperate with each other to improve the flame retardant performance of the filling material.
[0034] 3. The fire door filling material of the present invention uses polyethylene glycol-1000 as a soft block phthalic anhydride polyester polyol to dilute the viscosity of the pre-foamed material, making the reaction system easier to mix and process, thereby improving the uniformity and formability of the foam. The hydroxy silicone oil can reduce the surface tension of the system, making it easier for the gas to diffuse in the system and form uniform bubbles. The silicon-oxygen bond in the hydroxy silicone oil has a higher bond energy, so that the foam can still maintain good performance under high temperature and harsh environment. Urea is a nitrogen-containing organic substance that can react with isocyanate to generate allophanate. These intermediates can further participate in the formation of polyurethane chain segments, thereby adjusting the speed and process of the entire reaction, reducing the merging and rupture of bubbles, improving the uniformity and stability of the foam, increasing the rigidity and strength of the foam, and through curing and aging, allowing the incompletely reacted functional groups in the foam board material to continue to react until the reaction is complete, thereby promoting the release and balance of stress in the foam board, reducing the risk of deformation and cracking of the foam board, and further improving the chemical stability and structural strength of the foam board. The addition of urea increases the nitrogen content in the foam material, further increasing the flame retardant properties of the filling material. DETAILED DESCRIPTION
[0035] The technical scheme of the present invention will be clearly and completely described below in conjunction with the embodiments. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0036] The phthalic anhydride polyester polyol in this application has a density of 1.55 g / cm³, a viscosity of 2000-3000 mPa·s, an acid value of ≤3 mgKOH / g, and a hydroxyl value of 300±30 mgKOH / g;
[0037] The viscosity of the hydroxy silicone oil in this application is 15-30 mm 2 / s, and the hydroxyl content is 6-9%.
[0038] Embodiment 1:
[0039] This embodiment provides a method for preparing a fire door filling material, comprising the following steps:
[0040] S1. Preparation of modified mixed filler:
[0041] Weigh 5 parts of mullite fiber, 2 parts of hollow glass microspheres and 2 parts of expanded graphite by weight, mix them evenly to obtain a mixed filler;
[0042] Mix 0.3 mol / L sodium hydroxide solution and sodium stearate in a dosage ratio of 3 mL:1 g to obtain a catalyst for later use;
[0043] Weigh: 800 g of mixed filler, 4000 mL of tetrahydrofuran, and 600 g of KH-560, add into a three-necked flask and stir, raise the temperature of the three-necked flask to 55°C, add 1000 mL of catalyst into the three-necked flask, keep warm and react for 90 minutes, lower the temperature of the three-necked flask to room temperature, filter, wash the filter cake with purified water until it is neutral and then dry, transfer the filter cake to a drying oven at a temperature of 60°C, and vacuum dry it to constant weight to obtain a modified mixed filler.
[0044] S2. Preparation of modified phosphate ester:
[0045] Weigh: 250.6 g of diethyl (chlorocarbonyldifluoromethyl)phosphonate, 52.1 g of 1-(oxirane-2-yl)ethane-1,2-diol, 2506 mL of tetrahydrofuran and 76.0 g of potassium carbonate, add into a three-necked flask protected by nitrogen and stir, raise the temperature of the three-necked flask to 40°C, keep warm for 4 hours, keep the three-necked flask at 40°C, remove low-boiling substances under reduced pressure, lower the temperature of the reaction system to room temperature, add 1500 mL of anhydrous ethanol to the reaction system, lower the temperature of the three-necked flask to 5°C, stir and disperse for 20 minutes, filter, transfer the filtrate to a rotary evaporator with a water bath temperature of 60°C, remove low-boiling substances under reduced pressure, and obtain a modified phosphate.
[0046] S3. Preparation of composite filler:
[0047] Weigh: 600 g of modified mixed filler, 1200 g of PEG-400, 200 g of modified phosphate ester and 10000 mL of deionized water, add into a three-necked flask and stir, add phosphoric acid into the three-necked flask, adjust the system pH to 3, raise the temperature of the three-necked flask to 70°C, keep warm for 2 hours, lower the temperature of the three-necked flask to room temperature, filter, wash the filter cake with deionized water until it is neutral and then dry, transfer the filter cake to a drying oven at a temperature of 65°C, and vacuum dry to constant weight to obtain a composite filler.
[0048] S4, preparing foaming material:
[0049] Mix fluorodichloroethane, triethylenediamine and dipropylene glycol in a ratio of 5 g:2 g:7 mL to obtain a foaming aid for later use;
[0050] Weigh by weight: 55 parts of phthalic anhydride polyester polyol, 20 parts of polyethylene glycol-1000, 8 parts of hydroxy silicone oil, 15 parts of composite filler, 5 parts of urea, and 10 parts of foaming aid, add them into a beaker, stir and mix evenly, and obtain a pre-foamed material;
[0051] Nitrogen was introduced into the beaker for protection, and the amount of isophorone diisocyanate was calculated by measuring 1 / 2 of the total molar amount of hydroxyl groups and amino groups in the pre-foamed material, and added to the beaker containing the pre-foamed material, and stirred and dispersed until the pre-foamed material was generated by bubbles to obtain a foamed material.
[0052] S5. Preparation of filling materials:
[0053] The foaming material is injected into the mold, and after foaming and curing, a density of 0.15g / m 3 The foam board is placed in a curing box at a temperature of 80°C and a humidity of 60% for 10 hours, and then transferred to a drying box at a temperature of 60°C and dried to constant weight to obtain a filling material.
[0054] Embodiment 2:
[0055] This embodiment provides a method for preparing a fire door filling material, comprising the following steps:
[0056] S1. Preparation of modified mixed filler:
[0057] Weigh 5 parts of mullite fiber, 2 parts of hollow glass microspheres and 2 parts of expanded graphite by weight, mix them evenly to obtain a mixed filler;
[0058] 0.4 mol / L sodium hydroxide solution and sodium stearate were mixed uniformly at a dosage ratio of 3 mL:1 g to obtain a catalyst for later use;
[0059] Weigh: 800 g of mixed filler, 4000 mL of tetrahydrofuran, and 600 g of KH-560, add into a three-necked flask and stir, raise the temperature of the three-necked flask to 60°C, add 1000 mL of catalyst into the three-necked flask, keep warm and react for 105 minutes, lower the temperature of the three-necked flask to room temperature, filter, wash the filter cake with purified water until it is neutral and then dry, transfer the filter cake to a drying oven at a temperature of 65°C, and vacuum dry it to constant weight to obtain a modified mixed filler.
[0060] S2. Preparation of modified phosphate ester:
[0061] Weigh: 250.6 g of diethyl (chlorocarbonyldifluoromethyl)phosphonate, 52.1 g of 1-(oxirane-2-yl)ethane-1,2-diol, 2506 mL of tetrahydrofuran and 76.0 g of potassium carbonate, add into a three-necked flask protected by nitrogen and stir, raise the temperature of the three-necked flask to 43°C, keep warm for 5 hours, keep the three-necked flask at 43°C, remove low-boiling substances under reduced pressure, lower the temperature of the reaction system to room temperature, add 1500 mL of anhydrous ethanol to the reaction system, lower the temperature of the three-necked flask to 7°C, stir and disperse for 25 minutes, filter, transfer the filtrate to a rotary evaporator with a water bath temperature of 65°C, remove low-boiling substances under reduced pressure, and obtain a modified phosphate.
[0062] S3. Preparation of composite filler:
[0063] Weigh: 600 g of modified mixed filler, 1200 g of PEG-400, 200 g of modified phosphate ester and 10000 mL of deionized water, add into a three-necked flask and stir, add phosphoric acid into the three-necked flask, adjust the system pH to 3.5, raise the temperature of the three-necked flask to 75°C, keep warm for 2.5 hours, lower the temperature of the three-necked flask to room temperature, filter, wash the filter cake with deionized water until it is neutral and then dry, transfer the filter cake to a drying oven at a temperature of 70°C, and vacuum dry it to constant weight to obtain a composite filler.
[0064] S4, preparing foaming material:
[0065] Mix fluorodichloroethane, triethylenediamine and dipropylene glycol in a ratio of 5 g:2 g:7 mL to obtain a foaming aid for later use;
[0066] Weigh by weight: 60 parts of phthalic anhydride polyester polyol, 25 parts of polyethylene glycol-1000, 10 parts of hydroxy silicone oil, 17 parts of composite filler, 6 parts of urea, and 13 parts of foaming aid, add them into a beaker, stir and mix evenly, and obtain a pre-foamed material;
[0067] Nitrogen was introduced into the beaker for protection, and the amount of meta-xylylene diisocyanate was calculated based on 1 / 2 of the total molar amount of hydroxyl groups and amino groups in the pre-foamed material. The pre-foamed material was added to the beaker containing the pre-foamed material, and stirred and dispersed until the pre-foamed material was generated by bubbles to obtain a foamed material.
[0068] S5. Preparation of filling materials:
[0069] The foaming material is injected into the mold, and after foaming and curing, the density is 0.17g / m 3 The foam board is placed in a curing box at a temperature of 85°C and a humidity of 70% for 11 hours, and then transferred to a drying box at a temperature of 65°C and dried to constant weight to obtain a filling material.
[0070] Embodiment 3:
[0071] This embodiment provides a method for preparing a fire door filling material, comprising the following steps:
[0072] S1. Preparation of modified mixed filler:
[0073] Weigh 5 parts of mullite fiber, 2 parts of hollow glass microspheres and 2 parts of expanded graphite by weight, mix them evenly to obtain a mixed filler;
[0074] Mix 0.5 mol / L sodium hydroxide solution and sodium stearate in a ratio of 3 mL:1 g to obtain a catalyst for later use;
[0075] Weigh: 800 g of mixed filler, 4000 mL of tetrahydrofuran, and 600 g of KH-560, add into a three-necked flask and stir, raise the temperature of the three-necked flask to 65°C, add 1000 mL of catalyst into the three-necked flask, keep warm and react for 120 minutes, lower the temperature of the three-necked flask to room temperature, filter, wash the filter cake with purified water until it is neutral and then dry, transfer the filter cake to a drying oven at a temperature of 70°C, and vacuum dry it to constant weight to obtain a modified mixed filler.
[0076] S2. Preparation of modified phosphate ester:
[0077] Weigh: 250.6 g of diethyl (chlorocarbonyldifluoromethyl)phosphonate, 52.1 g of 1-(oxirane-2-yl)ethane-1,2-diol, 2506 mL of tetrahydrofuran and 76.0 g of potassium carbonate, add into a three-necked flask protected by nitrogen and stir, raise the temperature of the three-necked flask to 45°C, keep the reaction for 6 hours, keep the three-necked flask at 45°C, remove low-boiling substances under reduced pressure, lower the temperature of the reaction system to room temperature, add 1500 mL of anhydrous ethanol to the reaction system, lower the temperature of the three-necked flask to 10°C, stir and disperse for 30 minutes, filter, transfer the filtrate to a rotary evaporator with a water bath temperature of 70°C, remove low-boiling substances under reduced pressure, and obtain a modified phosphate.
[0078] S3. Preparation of composite filler:
[0079] Weigh: 600 g of modified mixed filler, 1200 g of PEG-400, 200 g of modified phosphate ester and 10000 mL of deionized water, add into a three-necked flask and stir, add phosphoric acid into the three-necked flask, adjust the system pH to 4, raise the temperature of the three-necked flask to 80°C, keep warm for 3 hours, lower the temperature of the three-necked flask to room temperature, filter, wash the filter cake with deionized water until it is neutral and then dry, transfer the filter cake to a drying oven at a temperature of 75°C, and vacuum dry to constant weight to obtain a composite filler.
[0080] S4, preparing foaming material:
[0081] Mix fluorodichloroethane, triethylenediamine and dipropylene glycol in a ratio of 5 g:2 g:7 mL to obtain a foaming aid for later use;
[0082] Weigh by weight: 65 parts of phthalic anhydride polyester polyol, 30 parts of polyethylene glycol-1000, 13 parts of hydroxy silicone oil, 18 parts of composite filler, 7 parts of urea, and 15 parts of foaming aid, add them into a beaker, stir and mix evenly, and obtain a pre-foamed material;
[0083] Nitrogen was introduced into the beaker for protection, and the amount of o-phenylenediisocyanate was calculated based on 1 / 2 of the total molar amount of hydroxyl groups and amino groups in the pre-foamed material. The pre-foamed material was added to the beaker containing the pre-foamed material, and stirred and dispersed until bubbles were generated in the pre-foamed material to obtain a foamed material.
[0084] S5. Preparation of filling materials:
[0085] The foaming material is injected into the mold, and after foaming and curing, the density is 0.18g / m 3 The foam board is placed in a curing box at a temperature of 90°C and a humidity of 80% for 12 hours, and then transferred to a drying box at a temperature of 70°C and dried to constant weight to obtain a filling material.
[0086] Comparative Example 1:
[0087] The difference between this comparative example and Example 3 is that no expanded graphite is added to the mixed filler in step S1.
[0088] Comparative Example 2:
[0089] The difference between this comparative example and Example 3 is that step S2 is eliminated and modified phosphate is not added in step S3.
[0090] Comparative Example 3:
[0091] The difference between this comparative example and Example 3 is that in step S3, PEG-400 is not added.
[0092] Comparative Example 4:
[0093] The difference between this comparative example and Example 3 is that in step S4, urea is not added.
[0094] Performance Test:
[0095] The combustion performance grades of the filling materials prepared in Examples 1-3 and Comparative Examples 1-4 were determined with reference to the standard GB 8624-2012 "Classification of Combustion Performance of Building Materials and Products";
[0096] The compressive stress of the filling materials prepared in Examples 1-3 and Comparative Examples 1-4 when the relative deformation was 10% was measured with reference to the standard GB / T 8813-2020 "Determination of compression properties of rigid foam plastics";
[0097] The sound absorption coefficients of the filling materials prepared in Examples 1-3 and Comparative Examples 1-4 were measured with reference to standard GB / T 18696.2-2002 "Measurement of sound absorption coefficient and acoustic impedance in acoustic impedance tubes Part 2: Transfer function method". The specific test results are shown in Table 1 below.
[0098] Table 1-Performance test data of the sample:
[0099] ;
[0100] Data Analysis:
[0101] A comparative analysis of the data in Table 1 above shows that the compressive stress of the filling material prepared by the present invention reaches 1905 kPa, the sound absorption coefficient reaches 0.84, the combustion performance grade reaches A1, and all performance parameters are better than those of the comparative example. The present invention optimizes the composition of the filler, mixes it with phosphate ester, and then uses polyethylene glycol to modify it to prepare a composite filler, and then mixes it with phthalic anhydride polyester polyol, polyethylene glycol-1000, and hydroxy silicone oil for foaming, which not only effectively improves the compression performance and sound absorption performance of the foamed material, but also improves the flame retardant properties of the material.
[0102] The preferred embodiments of the present invention disclosed above are only used to help explain the present invention. The preferred embodiments do not describe all the details in detail, nor do they limit the invention to specific implementation methods. Obviously, many modifications and changes can be made according to the content of this specification. This specification selects and specifically describes these embodiments to better explain the principles and practical applications of the present invention, so that those skilled in the art can understand and use the present invention well. The present invention is limited only by the claims and their full scope and equivalents.
Claims
1. A fire door filling material, characterized in that: The fire door filling material is obtained by processing the following steps: S1, mixing and stirring the modified mixed filler, polyethylene glycol, modified phosphate ester and deionized water, adding phosphoric acid to the reaction system, adjusting the system pH to 3-4, raising the temperature of the reaction system to 70-80°C, keeping the temperature for reaction for 2-3h, and post-treating to obtain a composite filler; S2, mixing phthalic anhydride polyester polyol, polyethylene glycol, hydroxy silicone oil, composite filler, urea, and foaming aid to obtain a pre-foamed material; S3, under the protection of inert gas, adding diisocyanate to the pre-foamed material, stirring and dispersing until the pre-foamed material is generated by bubbles, to obtain a foamed material; S4, injecting the foaming material into the mold, and curing it after foaming to prepare the filling material.
2. A fire door filling material according to claim 1, characterized in that: In step S1, the amount ratio of the modified mixed filler, polyethylene glycol, modified phosphate and deionized water is 3g:6g:1g:50mL, the polyethylene glycol is PEG-400, and the post-treatment includes: after the reaction is completed, the temperature of the reaction system is lowered to room temperature, filtered, the filter cake is washed with deionized water until it is neutral and then dried, the filter cake is transferred to a drying oven at a temperature of 65-75°C, and vacuum dried to constant weight to obtain a composite filler.
3. A fire door filling material according to claim 1, characterized in that: In step S2, the weight ratio of the phthalic anhydride polyester polyol, polyethylene glycol, hydroxy silicone oil, composite filler, urea and foaming aid is 55-65:20-30:8-13:15-18:5-7:10-15, the polyethylene glycol is PEG-1000, and the foaming aid is composed of monofluorodichloroethane, triethylenediamine and dipropylene glycol in a dosage ratio of 5g:2g:7mL.
4. A fire door filling material according to claim 1, characterized in that: In step S3, the molar amount of the diisocyanate is half of the total molar amount of the hydroxyl group and the amino group in the pre-foamed material, and the diisocyanate is one or more of isophorone diisocyanate, meta-phenylenediisocyanate, o-phenylenediisocyanate, toluene 2,6-diisocyanate, and meta-phenylenediisocyanate.
5. The fire door filling material according to claim 1, characterized in that: In step S4, the aging operation includes: placing the foamed and cured foam in a curing box at a temperature of 80-90°C and a humidity of 60-80% for aging for 10-12 hours, and then transferring it to a drying box at a temperature of 60-70°C and drying it to constant weight to obtain a filling material.
6. A fire door filling material according to claim 1, characterized in that: The modified mixed filler is processed by the following steps: A1, mixing mullite fiber, hollow glass microspheres and expanded graphite uniformly to obtain a mixed filler; A2. Mix and stir the mixed filler, tetrahydrofuran and KH-560, raise the temperature of the reaction system to 55-65°C, add a catalyst to the reaction system, keep the temperature for 90-120 minutes, and post-treat to obtain a modified mixed filler.
7. A fire door filling material according to claim 6, characterized in that: In step A1, the weight ratio of mullite fiber, hollow glass microsphere and expanded graphite is 5:2:2; in step A2, the amount ratio of the mixed filler, tetrahydrofuran, KH-560 and catalyst is 4g:20mL:3g:5mL, the catalyst is composed of 0.3-0.5mol / L sodium hydroxide solution and sodium stearate in an amount ratio of 3mL:1g, and the post-treatment includes: after the reaction is completed, the temperature of the reaction system is lowered to room temperature, filtered, the filter cake is washed with purified water until neutral and then dried, the filter cake is transferred to a drying oven at a temperature of 60-70°C, and vacuum dried to constant weight to obtain a modified mixed filler.
8. The fire door filling material according to claim 1, characterized in that: The preparation method of the modified phosphate ester is as follows: under the protection of inert gas, diethyl (chlorocarbonyldifluoromethyl)phosphonate, 1-(oxirane-2-yl)ethane-1,2-diol, tetrahydrofuran and potassium carbonate are mixed and stirred, the temperature of the reaction system is increased to 40-45°C, the reaction is kept warm for 4-6 hours, and post-processed to obtain the modified phosphate ester.
9. A fire door filling material according to claim 8, characterized in that: The dosage ratio of the diethyl (chlorocarbonyldifluoromethyl)phosphonate, 1-(oxirane-2-yl)ethane-1,2-diol and potassium carbonate is 2 mol:1 mol:1.1 mol, the dosage ratio of the diethyl (chlorocarbonyldifluoromethyl)phosphonate and tetrahydrofuran is 1 g:10 mL, and the post-treatment comprises: keeping the reaction system at 40-45° C., removing low-boiling substances under reduced pressure, lowering the temperature of the reaction system to room temperature, adding anhydrous ethanol to the reaction system, lowering the temperature of the reaction system to 5-10° C., stirring and dispersing for 20-30 minutes, filtering, transferring the filtrate to a rotary evaporator with a water bath temperature of 60-70° C., and removing low-boiling substances under reduced pressure to obtain a modified phosphate.
10. An application of a fire door filling material, characterized in that: The fire door filling material according to any one of claims 1 to 9 is applied to the manufacture of fire doors.
Citation Information
Patent Citations
Preparation method of brucite-based lightweight fireproof door filling material
CN107673728A
Environment-friendly high-flame retardance rigid polyurethane foam and preparation method and application thereof
CN101962474A
Halogen-free flame-retardant rigid polyurethane foamed plastic and preparation method for same
CN103694438A
Hollow glass micro-spheres surface modification method
CN104130597A
Hollow glass microsphere and preparation method thereof
CN107601828A